Strategies for Strengthening the Pancasila Student Profile to Foster Learning Motivation in Early Childhood Education Institutions - Efa Kurnia Suci; Ihlas Ihlas; Hermansyah Hermansyah (Universitas Sebelas Maret, 2026)
This study aims to analyze the strategy of strengthening the Pancasila Student Profile in fostering students’ learning motivation at PAUD Pelita. The focus of the study is directed at the implementation of Pancasila Student Profile values in learning activities and their contribution to the learning motivation of early childhood students. This research employed a qualitative approach with a descriptive method. Data collection techniques included observation of learning activities, interviews with teachers, and documentation. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results of the study indicate that strengthening the dimensions of the Pancasila Student Profile integrated into daily learning activities such as the habituation of moral behavior, cooperation, independence, creativity, and respect for diversity contributes positively to the development of students’ learning motivation. The indicators of learning motivation found in this study include increased enthusiasm in participating in activities, active engagement during the learning process, and the development of self-confidence in completing tasks and participating in classroom activities. These findings confirm that strengthening the Pancasila Student Profile at the early childhood education level not only functions as an implementation of curriculum policy but also serves as an effective pedagogical strategy in fostering intrinsic learning motivation in young children, as reflected in the learning practices carried out directly at PAUD Pelita.